In situ needle fenestration for aortic arch conditions during thoracic endovascular aortic repair - Gang Li; Minghui Li; Zhiqiang Dong; Jiaxi Gu; Hong Liu; Xinyang Xu; Weidong Gu; Yongfeng Shao; Buqing Ni (BMC Cardiovascular Disorders)
Abstract Background To evaluate the clinical outcomes and the validity of the in situ needle fenestration (ISNF) technique during thoracic endovascular aortic repair (TEVAR) for patients with aortic arch conditions. Methods A total of 115 patients with aortic arch conditions treated with ISNF during TEVAR between January 2018 and December 2021 were incorporated. Results The median age of the patients was 62.0 years, and 10.4% (12/115) were female. The median follow-up time was 31.0 months. A total of 175 supra-arch branches were reconstructed. A single branch was fenestrated in 80 patients, while the left subclavian artery (LSA) and left common carotid artery (LCCA) were fenestrated simultaneously in 11 patients, and all supra-arch branches were fenestrated in 24 patients. The rate of technical success was 100%, 30-day mortality was 3.5% (4/115), overall mortality was 8.7% (10/115), and aortic-related mortality was 2.6% (3/115). Aortic-related reintervention was required in 7.8% (9/115) of patients. Among the major postoperative complications, four patients developed retrograde type A dissection requiring emergent open surgery, three patients had cerebrovascular accidents, and one patient had an endoleak. No occlusions or stenoses of the main or branch aortic stents were observed. Conclusions The mid-term results of the ISNF technique during TEVAR for aortic arch conditions were within the acceptable range; however, further follow-up results are needed and long-term stability and durability needs to be assessed. Related fenestration devices also require further development.